2022
DOI: 10.1183/13993003.03101-2021
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training enhances recovery post-COVID-19: a randomised controlled trial

Abstract: BackgroundMany people recovering from COVID-19 experience prolonged symptoms, particularly breathlessness. We urgently need to identify safe and effective COVID-19 rehabilitative strategies. The aim of the current study was to investigate the potential rehabilitative role of inspiratory muscle training (IMT).Methods281 adults (46.6±12.2 years; 88% female) recovering from self-reported COVID-19 (9.0±4.2 months post-acute infection) were randomised 4:1 to an 8-week IMT or a “usual care” wait list control arm. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
193
2
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(209 citation statements)
references
References 43 publications
(59 reference statements)
5
193
2
9
Order By: Relevance
“…Moreover, the findings of the current study showed a statistically significant decrease in dyspnoea in favour of the study group, in which the MMRC scale decreased by 48.9% ( p < 0.001), whereas in the control group, it decreased by 12.8% ( p < 0.01). This is compatible with McNarry et al ( 35 ), who demonstrated that IMT can dramatically enhance long-term COVID patients’ dyspnoea, respiratory muscle function, and functional capacity. Furthermore, in recovered COVID-19 patients, Abodonya et al ( 14 ) found that IMT improved pulmonary functioning, dyspnoea, and fatigue, which is also supported by Nopp et al ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the findings of the current study showed a statistically significant decrease in dyspnoea in favour of the study group, in which the MMRC scale decreased by 48.9% ( p < 0.001), whereas in the control group, it decreased by 12.8% ( p < 0.01). This is compatible with McNarry et al ( 35 ), who demonstrated that IMT can dramatically enhance long-term COVID patients’ dyspnoea, respiratory muscle function, and functional capacity. Furthermore, in recovered COVID-19 patients, Abodonya et al ( 14 ) found that IMT improved pulmonary functioning, dyspnoea, and fatigue, which is also supported by Nopp et al ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
“…Though breathlessness is a common symptom of COVID-19 [1], progress of the respiratory impairments over time is not yet known. These results may indicate a need for respiratory follow-up after hospital discharge in these patients, also including respiratory physical therapy with inspiratory muscle training to manage breathlessness and regain inspiratory muscle function [32].…”
Section: Discussionmentioning
confidence: 92%
“…Although SARS-CoV-2 is primarily a respiratory infection, it is a multi-system disease (Merad et al, 2022), including the nervous system. Understanding how dysfunction affects different interacting organ systems is important for understanding this disease, and discovering the abnormal subcellular alterations in function is likely to be vital for developing effective treatment strategies.…”
Section: These Abnormalities On Objective Tests May Indicate Novel Av...mentioning
confidence: 99%